Java ME on Symbian OS inside the smartphone model - Hayun, Roy Ben.; Mason, Sam.; Arrowsmith, Gavin; Safari eBooks (Chichester, England ; Hoboken, N.J. : John Wiley, 2009)
"In this book, experts from Symbian, Nokia and Sun Microsystems expose the power of Java ME on Symbian OS. The book introduces programming with Java ME on Symbian OS, and also reveals what is found 'under-the-hood'"--Resource description page.
Kicking butt with Java technology on Symbian OS -- Fundamentals of Java ME MIDP programming -- Enter Java ME on Symbian OS -- Handling diversity -- Java ME SDKs for Symbian OS -- Designing advanced applications with MSA -- DoJa (Java for FOMA) -- Writing MIDP games -- Java ME best practices -- Java ME subsystem architecture -- Integration of Java ME and native APIs.
Description based on print version record.
Includes bibliographical references (p. [433]-434) and index.
Keywords: Smartphones -- Programming; Java (Computer program language); Symbian OS (Computer file); Electronic books